JAEPL, Vol. 3, Winter 1997-1998 - Alice G. Brand (Editor) (Journal of the Assembly for Expanded Perspectives on Learning, 1997)
Essays Regina Foehr. A Tribute to James Moffett. Miles Myers. Remembering James Moffett. Donald R. Gallehr. Reading Jim Moffett. Richard L. Graves. Jim, We Hardly Knew You. Regina Foehr. Memories of James Moffett. Sheridan Blau. A Reflection and Memoir. Betty Jane Wagner. Outliving Jim Moffett. C. Jan Swearingen. Doubting and Believing: The Hermeneutics of Suspicion in Contexts of Faith. A belief-centered pedagogy helps students infuse cultural values into adversarial modes of academic writing. Terri Pullen. Active Reciprocity: The Positive, Mindful Flow of Mental Energy. The construct of mindfulness relates to Eastern meditative practices, consciousness, quantum physics, and creativity. Janet M. Ellerby. Julia Kristeva and the Psychological Dynamics of Writing. By tapping into latent emotional dynamics, Kristeva's poststructuralist psychology offers a means to modify the cognitive order emphasized in academic discourse. Kristie S. Fleckenstein. The Osmotic Self and Language Arts Pedagogy. Educators should evolve a pedagogy that privileges a participatory self, in which ego boundaries are permeable. Thomas Dean. The Pedagogy of Place. The impending collapse of our civil society and natural environment necessitates a revised perspective on community. Paul Lewis. How Many Students Does it Take to Write a Joke? Humor Writing in Composition Courses. While calling attention to rhetorical principles and practices, humor writing can energize composition courses. Gina Brief-Elgins. Happiness and the Blank Page: Csikszentmihalyi's Flow in the Writing Classroom. Redefining happiness to include encounters with difficulty helps students embrace rather than dread arduous writing tasks.